Exploring The Motivation and Study Habits of Consistent BSED Science Major Deans Listers - Ramboy, Michelle; Sajulga, Aussien Angel; Gomez, Hanilie; Sombilon, Donna Fe; Tantog, Alfer Jann; Catubig, Daisy; Naparan, Genesis (Indonesian Journal of Education and Social Sciences, 2025)
This study employs a qualitative descriptive approach within a case study design to explore the motivations and study habits of consistent Dean’s Listers majoring in BSEd Science. Guided by Self-Determination Theory (Ryan & Deci, 2017), the research uses in-depth semi-structured interviews and Merriam’s analytical method to examine internal motivations and learning strategies. Eight participants, selected through purposive sampling, had consistently achieved Dean’s List status for at least three semesters. Thematic analysis revealed that academic validation, personal satisfaction, and scholarship incentives drive their performance. Common study habits include note-taking, early morning or late-night study, and group collaboration. Findings underscore the importance of intrinsic motivation and a supportive learning environment in sustaining academic success. While the study is limited to BSEd Science majors in one region, it provides meaningful insights into student achievement and offers practical implications for educators and policymakers aiming to strengthen science education.